Strategi Penanganan dan Pengembangan Usaha Ternak Sapi PO di Kawasan Penyangga Taman Nasional Baluran - Deby Okta Tyapradana; Siti Azizah (Yayasan Literasi Sains Indonesia, 2022)
The semi-extensive of Ongole Crossbreed cattle business has been carried out for generations by the people of Baluran National Park bufferzone area. The existence of abundant forage in the savanna is the main attraction for farmers and investors to get involved in this business. On the other hand, these activities are limited by legal aspects of national park management. The research was conducted on March, 11, 2021 – December, 23, 2021 used a mixed method squential exploratory model with purposive and exclusion samples. Data were obtained through observations in grazing areas and interviews based on a questionnaire to 60 respondents. The results showed that livestock farming was carried out under a profit-sharing system with 4,718 AU with total investor ownership of 2,608 AU (55.3%) and the highest forage yield during the rainy season was 766.5 gr/m2. Based on the available traditional and special areas of 2,397.29 Ha, the estimated maximum capacity during the rainy season is 805.5 AU. The results of the SOAR analysis are increasing the capacity of the role of area managers through the stages of forming fostered livestock groups and pilot cage, localizing limited grazing by area zoning arrangements, implementing a pasture grazing system, creating policies for dealing with illegal grazing and increasing socialization of intensive livestock farming with business schemes.